Time of disease and premedication as a risk for perforated appendicitis in ventanilla hospital, 2017: Tiempo de enfermedad y premedicación como riesgo para apendicitis perforada en el hospital de ventanilla 2017 - Cruz Díaz, Luis Augusto (2019)
Objective: To determine the time of illness and pre-medication as risk factors for perforated appendicitis in the Hospital of Ventanilla during the period of January - September 2017. Methods: An analytical study of type and control was carried out. The population consisted of 234 patients with their clinical histories, the group cases constituted by 78 patients with postoperative diagnosis of perforated appendicitis and the control group constituted by 156 patients with postoperative diagnosis with non-perforated appendicitis. Results: It was found that 61.5% of the patients with a disease time longer than 72 hours had perforated appendicitis (OR = 5.33, 95% CI (2.96, 9.61), p <0.001). 69.2% of patients with an out-of-hospital disease time longer than 24 hours presented perforated appendicitis (OR = 5.72, 95% CI: (3.16 - 10.37), p <0.001). 56.4% of patients with intrahospital disease time greater than 12 hours had perforated appendicitis (OR = 2.24 95% CI (1.29, 3.91) p <0.003). In relation to premedication, 15.4% of patients who took previous medications had perforated appendicitis (OR = 2.97, 95% CI (1.19, 7.39) p = 0.017). Conclusion: It is concluded that the time of illness and the premedication that in the majority of the unprescribed are risk factors for the presence ofperforated appendicitis. DOI:10.25176/RFMH.v19.n2.2071